A Phenomenological Study of Early Career School Counselor Clinical Supervision Experiences. Issue 1 (3rd March 2021) - Bledsoe, Kenya G.; Burnham, Joy J.; Cook, Ryan M.; Clark, Madeline; Webb, Alan L.
Researchers conducted a qualitative, phenomenological investigation of the clinical supervision experiences of nine early career school counselors using semi-structured interviews. Researchers discovered six themes and related subthemes regarding clinical supervision experiences, including (a) challenges, (b) support, (c) knowledge, (d) self-efficacy, (e) improved professional identity, and (f) improved counseling services. Implications for school counselors, counseling supervisors, and counselor educators are discussed.